2020
DOI: 10.1021/acsmedchemlett.0c00076
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Alginate Encapsulated LS180 Spheroid Model for Anti-colorectal Cancer Compound Screening

Abstract: Colorectal cancer is one of the leading causes of cancer-related deaths. A main problem for its treatment is resistance to chemotherapy, requiring the development of new drugs. The success rate of new candidate cancer drugs in clinical trials remains dismal. Three-dimensional (3D) cell culture models have been proposed to bridge the current gap between in vitro chemotherapeutic studies and the human in vivo, due to shortcomings in the physiological relevance of the commonly used two-dimensional cell culture mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Alginate beads containing HCT116 cells, a CRC cell line, have been previously used to demonstrate relative drug resistance and the effects of fluorouracil (5-FU) chemotherapy on CRC cells in 3D [ 125 ]. Treating HCT116 in alginate gels with paclitaxel showed a decrease in glucose uptake, cell proliferation and cell viability [ 126 ]. Both of these studies concluded that embedding CRC cells in alginate beads could be used to test chemotherapeutic drugs.…”
Section: Current 3d Models Of Crcmentioning
confidence: 99%
“…Alginate beads containing HCT116 cells, a CRC cell line, have been previously used to demonstrate relative drug resistance and the effects of fluorouracil (5-FU) chemotherapy on CRC cells in 3D [ 125 ]. Treating HCT116 in alginate gels with paclitaxel showed a decrease in glucose uptake, cell proliferation and cell viability [ 126 ]. Both of these studies concluded that embedding CRC cells in alginate beads could be used to test chemotherapeutic drugs.…”
Section: Current 3d Models Of Crcmentioning
confidence: 99%
“…Based on the previous experience of working with hydrogels an experiment was setup to determine the optimal cell seeding density (data not shown) 37 . Cells were embedded into a combination of collagen and fibrinogen in the following concentration range (7.5 x 10 5 , 8.5 x 10 5 , 9.5 x 10 5 , 1.0 x 10 6 , 1.5 x 10 6 and 2.0 x 10 6 cells/mL), 2.0 x 10 6 cells/mL was found to be the optimal seeding density.…”
Section: Determining Cell Seeding Densitymentioning
confidence: 99%
“…Other applications of the RWV technique comprise tissue engineering approaches for functional cardiac muscle from rat heart cells [64] or from mouse embryonic stem cells [65] as well as bone tissue engineering [66,67], chondrogenesis [68], connective tissue [69], pancreas [70], and Schwann cells [71]. A human vaginal epithelial cell model [72], a cytotrophoblast invasion model [73], and a human intestinal epithelial cells (INT-407) for implantation model [74] and human colorectal cancer cell lines were used (LS180) for compound screening [75]. More general studies such as that of Wrzesinski et al showed that metabolic reprogramming of 3D cultures is strongly influenced by hypoxia [76] and Chang et al studied the molecular mechanisms underlying the enhanced functions of 3D hepatocyte aggregates [62].…”
Section: Applications Based On Rotary Wall Vessel Systemsmentioning
confidence: 99%